Reflections from dual-mode alumni on the differences between distance and F2F education. (4th May 2017) - Fırat, Mehmet
ABSTRACT: The relevant literature is rich enough about the differences between distance and face to face education. However, the number of studies examining these differences from the viewpoint of dual-mode alumni, those graduated from both distance and face to face education programmes is limited. In this study, opinions of 33 dual-mode alumni from Turkey were analysed. As a result of an inductive content analysis, seven themes were determined. The themes relating to the differences between distance and face to face education were reputation, workload, experience, tuition fees, quality, procrastination and flexibility, respectively. Contrary to expectations, five out of seven themes were found out to be in favour of distance education. The theme of reputation consisted of the most important difference between distance and face to face education. Another interesting theme related to campus life was procrastination which is to the detriment of face to face education. At the end of the study, future research directions and practical implications are presented.